Magnetic Holes Observed in the Ring Current Region near the Equatorial Plane - Stepanova, M (Elsevier Ltd, 2018)
There is little knowledge about the appearance of local reductions of the magnetic field at the equatorial plane in the inner magnetosphere. Using data from the AMPTE/CCE satellite inside the ring current region, we studied local reductions of the Bz component of the geomagnetic field, which were followed by subsequent enhancements, as a function of geocentric distance. We selected 102 comparatively large-scale and quasi-stable reduction/enhancement events and obtained their radial and magnetic local time (MLT) distribution. We find that these structures are observed for all MLT in the ring current region. Moreover, the probability to observe reduction/enhancement structures increases with the increase of geomagnetic activity, as measured by the Dst, AE, and PC indexes, and with the increase of the interplanetary magnetic field Bz component and the solar wind velocity. Detailed analyses of some of the events show that reduction/enhancement structures might be caused by diamagnetic effects due to local quasi-stationary enhancements of plasma pressure, which are observed to develop simultaneously with the magnetic depressions. © 2017 Elsevier Ltd